PENDAMPINGAN BIMBINGAN TEKNIS PENULISAN DAN PENERJEMAHAN CERITA ANAK DWIBAHASA DI KOTA DUMAI - Windayani; Muhammad Farid Firdaus; Faizal Nurmatias; Dina Liana; Zaitun Abidin; Mukhammad; Nurhayati; Ahmad Denico (DEVELOPMENT: Journal of Community Engagement, 2025)
This community service activity aims to improve the skills of teachers, students, and literacy communities in Dumai City in writing and translating bilingual children’s stories. The background of this activity lies in the limited availability of high-quality children’s reading materials in two languages, while literacy needs and foreign language proficiency are becoming increasingly urgent in the global era. The implementation method was carried out through technical guidance (training), which included workshops on children’s story writing, mentoring in translation into a second language, as well as peer review and revision sessions. The results of the activity showed an improvement in participants’ competencies, both in understanding the structure of children’s stories, techniques for composing simple language, and communicative translation strategies. Several bilingual children’s stories were successfully produced as final outputs, which have the potential to be developed into teaching materials or children’s reading resources in schools and the community. Thus, this mentoring program has proven effective in supporting the strengthening of a literacy culture and fostering the community’s creative spirit in producing bilingual children’s literature.